2008
DOI: 10.1002/chem.200801395
|View full text |Cite
|
Sign up to set email alerts
|

Oligosubstituted Pyrroles Directly from Substituted Methyl Isocyanides and Acetylenes

Abstract: The formal cycloaddition of alpha-metallated methyl isocyanides 1 onto the triple bond of electron-deficient acetylenes 2 represents a direct and convenient approach to oligosubstituted pyrroles 3. The scope and limitations of this reaction (24 examples, 25-97% yield) are reported along with an optimization of the reaction conditions and a rationalization of the mechanism. In addition, a related newly developed Cu(I)-mediated synthesis of 2,3-disubstituted pyrroles by the reaction of copper acetylides derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 141 publications
2
44
2
3
Order By: Relevance
“…However, following the initial report in 1979, 79 there was a long period of silence. 82 Obviously, this approach was not practical. Unfortunately, this protocol was not applicable to more abundant, non-activated terminal alkynes.…”
Section: Cycloaddition and Cyclizationmentioning
confidence: 99%
“…However, following the initial report in 1979, 79 there was a long period of silence. 82 Obviously, this approach was not practical. Unfortunately, this protocol was not applicable to more abundant, non-activated terminal alkynes.…”
Section: Cycloaddition and Cyclizationmentioning
confidence: 99%
“…The reaction mechanism is outlined in Scheme 8.112. [310,311]. The best results were achieved with Cu(I) benzenethiolate or preactivated nanosized copper powder (Cu 0 -NP) catalysts.…”
Section: %mentioning
confidence: 74%
“…A recent work from de Meijeres group revealed that this issue can be resolved by employing stoichiometric amounts of a slightly modified Cu(I) system. Accordingly, terminal alkynes 326 were shown to undergo the Cu(I)-mediated formal [ [311].…”
Section: %mentioning
confidence: 99%
“…Several copper could catalyze the polysubstituted pyrrole formation. Moreover, they also developed a new copper catalyst system for the synthesis of 2,3-disubstituted pyrroles by the reaction of copper acetylides derived from unactivated terminal alkynes with substituted methyl isocyanides in 5-88% yield [16,17]. The regiocontrolled formation of pyrroles via a formal [3+2] cycloaddition of isocyanides and electron-deficient alkynes could be realized in different catalytic system.…”
Section: Copper-catalyzed Synthesis Of Pyrrolesmentioning
confidence: 99%